1987
DOI: 10.1136/adc.62.10.1068
|View full text |Cite
|
Sign up to set email alerts
|

Mean arterial blood pressure and neonatal cerebral lesions.

Abstract: figure). Arterial waveforms were collected over 20 second periods and the true mean arterial pressure (MAP) derived. Data were stored on floppy disk and the 20 second cycles repeated. Ultrasound scans were made at least daily during the first week and then weekly until discharge, with an ATL Mark III sector scanner with multifrequency head (3/5/7.5 MHz).Thirty three infants were entered into the study; 28 were having mechanical ventilation, and five required headbox oxygen for the respiratory distress syndrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
178
1
6

Year Published

2001
2001
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 342 publications
(191 citation statements)
references
References 5 publications
6
178
1
6
Order By: Relevance
“…In preterm infants it is associated with the development of intraventricular hemorrhage (IVH), periventricular leukomalacia (PVL) and poor neurodevelopmental outcomes. [1][2][3][4] Inadequate perfusion as a complication of sepsis, respiratory failure, severe birth depression or persistent pulmonary hypertension, is also detrimental to the critically ill term infant. While the etiologies of hypotension are multifactorial, there may exist a subset of infants with adrenal insufficiency manifesting as hypotension refractory to standard therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In preterm infants it is associated with the development of intraventricular hemorrhage (IVH), periventricular leukomalacia (PVL) and poor neurodevelopmental outcomes. [1][2][3][4] Inadequate perfusion as a complication of sepsis, respiratory failure, severe birth depression or persistent pulmonary hypertension, is also detrimental to the critically ill term infant. While the etiologies of hypotension are multifactorial, there may exist a subset of infants with adrenal insufficiency manifesting as hypotension refractory to standard therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several studies have found an association between hypotension 9-12 and alterations in CBF [13][14][15] and central nervous system morbidity (IVH, PVL) and neurodevelopmental outcome. [16][17][18] However, it is important to note that, although data on an association between hypotension and/or abnormal CBF and short-and long-term central nervous system morbidity are abundant, [8][9][10][11][12][13][14][15][16][17][18] very little data are available demonstrating a causative relationship among these factors.…”
Section: Introductionmentioning
confidence: 99%
“…Hypotension is believed to be an important risk factor for cerebral ischemic injury and intracranial hemorrhage, and so preterm infants often receive volume expanders (even in the absence of hypovolemia) and/or inotropic drugs (most commonly, dopamine) to increase blood pressure (1,18). However, concern has been raised about whether these management practices could be detrimental (29).…”
mentioning
confidence: 99%